A Diglossia Phenomenon in Sasak Language Spoken by the Noblemen of Mambalan - Abdussamad, Zainudin; Syarifaturrahman, Wahyu Kamil; Sutarman, Sutarman; Supatmiwati, Diah (Humanitatis : Journal of Language and Literature, 2024)
This study aims to determine the language used and the diglossia situation among the members of the aristocracy of Mambalan Village, Gunung Sari District, West Nusa Tenggara. The approach used in this study is descriptive qualitative, which applies descriptive methods. Data collection techniques in this study are literature, observation, interviews, recording techniques, and note-taking. Data on diglossia are seen from seven domains: family domain, social domain, buying and selling transaction domain, religious domain, government domain, education domain, and profession domain. Based on research findings show that the aristocracy of Mambalan Village is bilingual and multilingual. This can be seen from the variety of languages used, namely Sasak alus language, Sasak jamak language, and Indonesian. This condition supported the occurrence of the diglossia situation among them. The study’s results based on the family domain show that the aristocracy of the Mambalan village still uses the Sasak alus and Indonesian as a high language (H). In the buying and selling transactions, it can be seen that the Sasak alus language and Indonesian are the high language (H) and most dominant languages used by the noblemen of Mambalan village. In the religion domain, especially when sermons in the mosque are more dominant in using Indonesian as a high language (H). While in the government, education, and professional domains it is more dominant in using Indonesian as a high language variety (H).